Material properties and residual stresses of S690 high strength steel welded PI-shaped and cruciform sections - Tay, Valerie Hui Fang (Nanyang Technological University, 2023)
This report presents an experimental study and review of the behaviour and characteristics of welded S690 high strength pi and cruciform steel section members. Ten specimens were fabricated from S690 steel plates using the method of gas metal arc welding (GMAW), which include 2 samples of each of the steel section members respectively. To investigate and understand the behaviour and characteristics of the steel sections, tests such as residual stress measurements and material coupon tests were conducted. The data results were then obtained and evaluated against existing design codes (Eurocode, Australian Standard and AISC) to verify and improve the design specifications on the current design codes of high strength steel. After which, two models are being proposed based on the data results obtained.